PROSES BERPIKIR KEMAMPUAN KONEKSI MATEMATIS PESERTA DIDIK DI SEKOLAH MENENGAH PERTAMA - Dilla Dalilah Fitri; AA Gde Somatanaya; Siska Ryane Muslimin (Journal of Authentic Research on Mathematics Education (JARME), 2019)
The aim of this research is to know the junior high school students’ thinking process of mathematical connections and the students’ error in problem solving with the two-dimensional solid material (cube and rectangular prisms). The research method was descriptive qualitativemethod. The instruments used in this research were a test of mathematical connections ability and an interview guidance. The qualitative data analysis used data reduction, data display, anddrawing conclusions and verification. The conclusions gained from this research are (1) students’ thinking process with high and middle ability in solving the problem about mathematical connections in daily life along with the connections between mathematical ideas have passed thestep of complete thinking process such as constructing meanings, constructing opinions, and drawing conclusions/making decisions. However, there are only students with high and middle ability who can complete the step of thinking process in solving problems about the connections between the mathematical topics and other studies while students with low ability cannot pass the complete step of thinking process; they can only construct the meanings, (2) the students’ errorin problems solving occur in making mathematical model; they do not write down the mathematical model and incompletely write the variable examples used in making the model, and also in solving mathematical model, particularly in substituting the value of perhitungan processand writing the wrong answers in the end of the question of the test.